Chronic Puerperal Uterine Inversion : A Case Report - Sharmin, Shahanaj; Alam, Didarul; Begum, Moquaddes Akter; Ahmed, Mohiuddin (Journal of Chittagong Medical College Teachers’ Association, 2013)
Inversion of utirus in a life threatening condition with a mortality rate of about 15%- We report an uncommon case of chronic puerperal uterine inversion. Our case is a 35-years old patient, para three full term normal vaginal deliveries reported to the gynecological outpatient department of Bangabandhu Memorial Hospital, University of Science & Technology Chittagong (USTC) Chittagong with a history of irregular per vaginal bleeding, sensation of something coming down per vagina, offensive vaginal discharge and anemia since her last delivery twelve years ago. A thorough clinical examination and radiological investigation including ultrasonography revealed chronic complete(stage II) puerperal Uterine inversion. The patient was treated with laparotomy followed by Haultain procedure subsequently hysterectomy done. We present one such case due to the rarity of this condition and the diagnostic dilemma it presents in the non puerperal stage. JCMCTA 2013; 24 (1):64-66